Design Thinking in Higher Education: Opportunities and Challenges for Decolonized Learning - Lake, Danielle; Guo, Wen; Chen, Elizabeth; McLaughlin, Jacqui (Teaching and Learning Inquiry, 2024)
This article builds upon current research to understand the value and limitations of teaching and learning design thinking (DT) in higher education. We implemented a mixed-methods study with faculty and students across 23 diverse courses in four higher education institutions in the United States. Findings showed that following structured learning processes, engaging in active listening, and focusing on others’ perspectives were the most valued DT practices across disciplines. In contrast, prototyping and experimentation were the least used DT practices, with widely varying understandings across disciplines. Additionally, we found consistent evidence that DT can support liberatory teaching and learning practices that decolonize students’ perceptions of power, encourage situated and action-oriented empathy, and provide opportunities for co-creation. This is particularly true when faculty intentionally encourage collaboration and project framing focused on critically analyzing dominant ways of knowing and power structures. Our analysis further revealed the challenges and importance of prototyping and conducting experiments with project partners. Ultimately, this approach can significantly enhance liberatory project outcomes and facilitate decolonized learning experiences. Given our findings, we point out limitations and challenges across current DT pedagogical practices and provide recommendations for integrating DT practices across disciplines in ways that center on issues of systemic oppression, social identity, and human-environmental relationships. Read the corresponding ISSOTL blog post here.